HETERONORMATIVE AESTHETICS IN ART CLASSES: OVERCOMING BY THE OPERATIVE GROUP - Camargo, Danielle Twerznik; Marques, Antonio Francisco [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
To observe a heteronormativity in educating behavior in art classes in a public school in the interior of Sao Paulo, an educator and a researcher proposing communication strategies and their consequences of segregation in the school environment. Thus, the general objective was to build to overcome the prejudice that comes from the practices, building the Operational Groups with a Social Psychology approach. As a specific objective, we propose an application of a Didactic Sequence and a socialization of the procedures in a site. It was concluded that the students had more tolerant positions after work, but a data collection denoted the need to rethink how heteronormative practices that perpetuate in the school.
Keywords: Heteronormativity; Art; Group; Social Psychology